Analysis of the Implementation of SAK EMKM in the Café Roxx Area MSMES in South Tondano District - Moroki, Florence Olivia; Evinita, Lenny Leorina; Salma Korompi, Rizky Ismail (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
This research aims to determine the application of SAK EMKM in the UMKM Cafe Roxx Area in Tondano Selata District, it is interesting to study to find out, the application of financial reports based on SAK EMKM in these MSMEs, The use oif finainciail repoirts baised oin SAK EMKM in these MSMEs. The reseairch wais coinducted using ai quailitaitive methoid which leaids toi the descriptioin aind aipplicaitioin oif finainciail recoirds baised oin SAK EMKM by coinducting interviews aiboiut finainciail repoirts toi be proicessed toi coimply with SAK EMKM. The results oif this reseairch shoiw thait: the UMKM Caiffe Roixx Areai oinly cointaiins recoirds oif incoime aind expenditure froim the results oif its business, the UMKM Caife Roixx Areai boioikkeeping repoirts doi noit haive ai sepairaitioin between liaibilities aind equity, aind there is noi sepairaitioin oif incoime taix, whereais the SAK EMKM explaiins thait there aire three coimpoinents. naimely the staitement oif finainciail poisitioin, proifit aind loiss staitement, aind noites toi the finainciail staitements in the staitement oif finainciail poisitioin, there is ai sepairaitioin between fixed aissets aind current aissets, liaibilities, aind, equity, while the proifit aind loiss repoirt hais ai sepairaitioin oif incoime, expenses aind incoime taixes.